Perkembangan Pendidikan Non Formal di Era Merdeka Belajar - Syufa’ati, Syufa’ati; Nadhifah, Nailun (Yayasan Darussalam Bengkulu, 2020)
Non-formal education is one of the education channels outside formal education. This aims to be able to keep up with the increasingly fast world development, and to answer the needs of situations and conditions, including in the current era of independent learning. The education policy for independent learning was implemented by the minister of education and culture (Kemendikbud) as a response to the need for the education system in the revolutionary era 4.O. The purpose of this study was to understand the development of non-formal education as a learning method for students in the independent learning era. This research uses library research (library research). With data sources from journals, research reports, news, books, and so on. So in this case, the development of non-formal education is part of the success of education in the era of independent learning. The reason is that in the era of independent learning, the learning process is not sufficient to only focus on formal education. Therefore, non-formal education with personally regulated regulations offers additional learning convenience for students.